Sapphic fathers: Discourses of same-sex desire from nineteenth-century France - Schultz, Gretchen (University of Toronto Press, 2014)
Literature that explored female homosexuality flourished in late nineteenth-century France. Poets, novelists, and pornographers, whether Symbolists, Realists, or Decadents, were all part of this literary moment. In Sapphic Fathers, Gretchen Schultz explores how these male writers and their readers took lesbianism as a cipher for apprehensions about sex and gender during a time of social and political upheaval. Tracing this phenomenon through poetry (Baudelaire, Verlaine), erotica and the popular novel (Belot), and literary fiction (Zola, Maupassant, Péladan, Mendès), and into scientific treatises, Schultz demonstrates that the literary discourse on lesbianism became the basis for the scientific and medical understanding of female same-sex desire in France. She also shows that the cumulative impact of this discourse left tangible traces that lasted well beyond nineteenth-century France, persisting into twentieth-century America to become the basis of lesbian pulp fiction after the Second World War.
Keywords: amériques; approches et analyses; arts; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis; études littéraires

L'identité de genre dans les oeuvres de George Sand et Colette - Krauthaker, Marion (L'Harmattan, 2011)
George Sand et Colette sont connues pour avoir publié des ouvrages dévoilant un grand modernisme et un engagement sur la question des relations entre les sexes. Cet ouvrage dévoile qu'alors que le XIXe et le début du XXe siècle se focalisaient surtout sur des revendications féministes visant la libération des femmes, ces deux auteures cherchaient aussi à dénoncer les codes traditionnellement imposés à tous les individus et à leur identité. Alors que le concept d'identité de genre n'était pas clairement théorisé à l'époque, leurs écrits suggèrent que Sand et Colette avaient déjà l'intuition que les hommes comme les femmes pouvaient être victimes des lois sociales fondées sur la différence sexuelle. Elles dénonçaient les limites que la société imposait aux sujets selon leur sexe et subvertissaient les schémas traditionnels de la formation identitaire. Pour cela, elles présentaient souvent la bipolarité des structures patriarcales comme une construction artificielle, elles mettaient en scène de nouveaux modèles de "féminité", de "masculinité" et de sexualité et elles démontraient une indéniable volonté de rupture et de remise en cause des traditions. Cette étude met aussi en évidence comment ces subversions successives peuvent être lues comme des présentations très modernes d'une identité de genre perçue comme une structure en constante mutation qui désavoue les inscriptions traditionnelles et normalisées. De manière étonnante, les illustrations d'expressions identitaires individuelles et plurielles chez Sand et l'élaboration d'un nouvel ordre des identités chez Colette rapprochent leurs écrits de théorisations contemporaines du genre.
Keywords: approches et analyses; arts; corps; discipline; europe; france; genre; histoire et politique; hétérosexisme; littérature; patriarcat; ressource en ligne; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; études littéraires

Lesbian empire: Radical crosswriting in the Twenties - Wachman, Gay (Rutgers University Press, 2001)
Gay Wachman provides a critical new reading of sexually radical fiction by British women in the years during and after the First World War. She contrasts works by Sylvia Townsend Warner, Virginia Woolf, Rose Allatini, and Evadne Price with more politically and narratively conservative novels by Radclyffe Hall and Clemence Dane. These writers, she states, formed part of an alternative modernist tradition that functioned both within and against the repressive ideology of the British Empire, using fantasy as a means of reshaping and critiquing a world fragmented by war. Wachman places at the center of this tradition Sylvia Townsend Warner's achievement in undermining the inhibitions that faced women writing about forbidden love. She discusses Warner's use of crosswriting to transpose the otherwise unrepresentable lives of invisible lesbians into narratives about gay men, destabilizing the borders of race, class, and gender and challenging the codes of expression on which imperialist patriarchy and capitalism depended.
Keywords: amour interdit; approches et analyses; arts; discipline; europe; littérature; patriarcat; personnes lesbiennes; racisme; royaume-uni; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; transgression; études littéraires

Romance revisited - Pearce, Lynne; Stacey, Jackie (New York University Press, 1995)
Après des décennies de féminisme et de déconstruction, la romance reste fermement ancrée comme une préoccupation centrale dans la vie de la plupart des femmes. Les taux de divorce montent en flèche, la famille traditionnelle est remise en question de toutes parts et pourtant la romance semble indestructible. En termes de représentation culturelle, la popularité de la romance semble également incontestée. La fiction populaire, le cinéma hollywoodien, les feuilletons télévisés et les médias en général affichent tous un appétit apparemment sans limite pour les sujets romantiques. Les pièges de la romance classique – mariages blancs, chansons d’amour, Saint-Valentin – sont plus que jamais commercialement viables. Dans cette anthologie d'essais originaux, la romance est revisitée sous un large éventail de perspectives, non seulement dans la fiction et le cinéma, mais dans toute une gamme de phénomènes culturels. Les essais couvrent des sujets tels que la Saint-Valentin, les relations interraciales, les visions érotiques médiévales et la fiction romantique moderne, la relation entre la poétesse lesbienne HD et Bryher, la blancheur omniprésente du désir romantique, l'érotisme lesbien à l'ère du SIDA et la romance publique de Charles et Diane.
Keywords: anthologie; approches et analyses; arts; classisme; discipline; histoire et politique; outils; ouvrages de références; patriarcat; racisme; romance; sexisme; sexualité; systèmes d'oppressions; thématiques; études culturelles; études littéraires

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Number: 3
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques